Practices of Anti-consumerism & Anti-consumption in Marketing - Varalakshmi, S.; Venkadeshwaran, K. (Current Aspects in Business, Economics and Finance Vol. 7, 2023)
Most of the world is thought to be residing in a consumption-driven socioeconomic period that is governed by powerful governments and companies. As a result, producers boost their output, contributing to economic growth. Thus, increased consumption and a change in lifestyle result in an excessive use of resources and environmental deterioration. Instead of why people choose a certain product or brand over another, research has mostly concentrated on why consumers choose a certain product or brand. With a thorough assessment of the types, lifestyles, effects, and trends in the anti-consumption sector, this chapter seeks to better explain the concept. The study's overarching goal is to assist marketers in aligning their initiatives with the sector by offering crucial data regarding anti-consumerists, a little-known group.